The essential blended learning PD planner: where classroom practice meets distance learning - Mekhitarian, Stepan (Corwin teaching essentials, 2021)
"This book will help educators capitalize on the skills and capacity built during remote learning to implement effective blended learning models in the classroom setting. The book will cover the integration of instructional technology, effective approaches to collaboration, professional development, assessment, feedback, digital citizenship and differentiated instruction. Most importantly, Mekhitarian will address how the effective implementation of blended learning across schools and systems can impact equity and access for all students"--